The Bloomsbury Handbook to the Digital Humanities - O'Sullivan, James 1986- (Bloomsbury Handbooks Ser., 2023)
Cover -- Contents -- List of Figures -- About the Editor -- List of Contributors -- Acknowledgments -- Introduction: Reconsidering the Present and Future of the Digital Humanities James O'Sullivan -- Part 1 Perspectives &amp -- Polemics -- 1 Normative Digital Humanities Johanna Drucker Johanna Drucker -- 2 The Peripheries and Epistemic Margins of Digital Humanities Domenico Fiormonte and Gimena del Rio Riande -- 3 Digital Humanities Outlooks beyond the West Titilola Babalola Aiyegbusi and Langa Khumalo -- 4 Postcolonial Digital Humanities Reconsidered Roopika Risam -- 5 Race, Otherness, and the Digital Humanities Rahul K. Gairola -- 6 Queer Digital Humanities Jason Boyd and Bo Ruberg -- 7 Feminist Digital Humanities Amy E. Earhart -- 8 Multilingual Digital Humanities Pedro Nilsson-Fernàndez and Quinn Dombrowski -- 9 Digital Humanities and/as Media Studies Abigail Moreshead and Anastasia Salter -- 10 Autoethnographies of Mediation Julie M. Funk and Jentery Sayers -- 11 The Dark Side of DH James Smithies -- Part 2 Methods, Tools, &amp -- Techniques -- 12 Critical Digital Humanities David M. Berry -- 13 Does Coding Matter for Doing Digital Humanities? Quinn Dombrowski -- 14 The Present and Future of Encoding Text(s) James Cummings -- 15 On Computers in Text Analysis Joanna Byszuk -- 16 The Possibilities and Limitations of Natural Language Processing for the Humanities Alexandra Schofield -- 17 Analyzing Audio/Visual Data in the Digital Humanities Taylor Arnold and Lauren Tilton -- 18 Social Media, Research, and the Digital Humanities Naomi Wells -- 19 Spatializing the Humanities Stuart Dunn -- 20 Visualizing Humanities Data Shawn Day -- Part 3 Public Digital Humanities -- 21 Open Access in the Humanities Disciplines Martin Paul Eve -- 22 Old Books, New Books, and Digital Publishing Elena Pierazzo and Peter Stokes.